Agroclimatic indicator analysis under climate change conditions to predict the climatic suitability for wheat production in the upper blue nile basin, Ethiopia - Demissew, Wondimeneh Leul; Zeleke, Tadesse Terefe; Ture, Kassahun; Mengistu, Dejene; Fufa, Meaza Abera (MDPI, 2025)
Agricultural productivity is significantly influenced by climate-related factors. Understanding the impacts of climate change on agroclimatic conditions is critical for ensuring sustainable agricultural practices. This study investigates how key agroclimatic variables—temperature, moisture conditions, and length of the growing season (LGS)—influence wheat suitability in the Upper Blue Nile Basin (UBNB), Ethiopia. The Global Agroecological Zones (GAEZ) methodology was employed to assess agroclimatic suitability, integrating climate projections from Climate Models Intercomparison Project v6 (CMIP6) under shared socioeconomic pathway (ssp370 and ssp585) scenarios. The CMIP6 data provided downscaled projections for temperature and precipitation, while the GAEZ framework translated these climatic inputs into agroclimatic indicators, enabling spatially explicit analyses of land suitability. Projections indicate significant warming, with mean annual temperatures expected to rise between 1.13 ◦C and 4.85 ◦C by the end of the century. Precipitation levels are anticipated to increase overall, although spatial variability may challenge moisture availability in some regions. The LGS is projected to extend, particularly in the southern and southeastern UBNB, enhancing agricultural potential in these areas. However, wheat suitability faces considerable declines; under ssp585, the highly suitable area is expected to drop from 24.21% to 13.31% by the 2080s due to thermal and moisture stress. This study highlights the intricate relationship between agroclimatic variables and agricultural productivity. Integrating GAEZ and CMIP6 projections provides quantified insights into the impacts of climate change on wheat suitability. These findings offer a foundation for developing adaptive strategies to safeguard food security and optimize land use in vulnerable regions.